Phytosociological survey of weeds in irrigated maize fields in a Southern Guinea Savanna of Nigeria - Salaudeen, Muhammadu Tajudeen; Daniya, Emmanuel; Olaniyi, Olayemi Mikail; Folorunso, Taliha Abiodun; Bala, Jibril Abdullahi; Abdullahi, Ibrahim Mohammed; Nuhu, Bello Kontagora; Adedigba, Adeyinka Peace; Oluwole, Blessing Israel; Bankole, Abdullah Oreoluwa; Macarthy, Odunayo Moses (Frontiers in Agronomy, 2022)
Maize is a food crop for millions of people in sub-Saharan Africa. However, severe weed infestation might cause significant yield loss. This study investigated weed composition, abundance and distribution in maize-based cropping systems in the Southern Guinea Savanna of Nigeria. Fields were surveyed between February and March 2022. The Importance Value Index (IVI) of each weed species was determined using relative frequency, relative density, and relative abundance. A total of 29 weed species from 15 families were identified. Poaceae (34.9 %) was the most prevalent weed family, followed by Cyperaceae (26.9 %) and Portulacaceae (12.8 %). The IVI showed that Cyperus rotundus (38.6), Portulaca oleraceae (29.4), Digitaria horizon-talis (25.5), Brachiaria deflexa (24.2), Senna obtusifolia (17.6), Ageratum co-nyzoides (16.0), Cynodon dactylon (12.6), Phyllanthus niruri (11.1) and Eragrostis sp. (10.6) were the most dominant. Principal Component Analysis (PCA) ordination biplot revealed that Setaria pumila was strongly associated with sole maize cultivation, as was Desmodium scorpiurus with maize/rice intercropping, C. dactylon with maize/pepper, Euphorbia hirta with maize/cassava, and Cleome viscosa with maize/amaranthus intercropping. Special attention to these weed species is required when making an informed decision on the choice of weed control measures.to reduce yield losses in endemic areas.